2021
DOI: 10.3892/etm.2021.10800
|View full text |Cite
|
Sign up to set email alerts
|

Expression and role of interleukin‑1β and associated biomarkers in deep vein thrombosis

Abstract: Lower extremity deep vein thrombosis (DVT) is a common peripheral vascular disease, in which inflammation plays an important role. The aim of the present study was to investigate the expression and role of inflammatory factors in DVT. A rat model of venous thrombosis of the lower extremities was established through venous ligation surgery. The rats were examined at 2, 8, 24, 48 and 72 h after the induction of inferior venous stenosis and compared with control and sham surgery groups. The serum levels of interl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…The apoptosis of HUVECs was inhibited by lncRNA XIST knockdown via miR-30c-5p/PTEN axis in atherosclerosis [ 39 ]. The TF level associated with dilated cardiomyopathy was improved through lncRNA XIST/miR-195-5p/NOVA1 axis [ 40 ], and the high level of TF facilitated thrombi formation in DVT patients [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The apoptosis of HUVECs was inhibited by lncRNA XIST knockdown via miR-30c-5p/PTEN axis in atherosclerosis [ 39 ]. The TF level associated with dilated cardiomyopathy was improved through lncRNA XIST/miR-195-5p/NOVA1 axis [ 40 ], and the high level of TF facilitated thrombi formation in DVT patients [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β is one of the most prominent inflammatory mediators leading to fever and immune activation by binding to IL-1 receptor 1 ( 77 ). A previous study reported that serum IL-1β level and IL-1β mRNA expression increased in thrombus tissue at 24 h in a stasis rat model ( 78 ). However, it was not shown which cells in the thrombus IL-1β originates from ( 78 ).…”
Section: Various Factors Associated With Monocytes/macrophages Affect...mentioning
confidence: 97%
“… 23 Another study has demonstrated that elevated levels of inflammatory factors interleukin-1β (IL-1β), tissue factor (TF), xanthine oxidase (XOD) and nuclear factor kappa B (NF-κB) may accelerate thrombosis. 26 The NLRP3/IL-1/NF-κB signaling mechanisms regulate IL-1 and tumor necrosis factor alpha (TNF-α), which may be essential signs of the prethrombotic condition due to slowed blood flow, impaired vascular endothelium, and elevated tissue factor expression. Therefore, VTE is the result of the coagulation system’s cascade reaction.…”
Section: Inflammatory Factormentioning
confidence: 99%